Self-initiated photocatalytic polymerization of tough and flexible polyacrylamide hydrogel/polymeric semiconductor c3n4composites - Suphatchaya Lamkhao (2018)
© 2017, Tokai University. All rights reserved. Polyacrylamide (PAM)/g-C3N4composite materials were prepared by the self-initiation of C3N4via its photocatalytic activity. Radical species were produced during illumination of g-C3N4and can initiate the formation of the PAM/C3N4composite. The effect of charcoal composited to C3N4was also investigated. The physical properties of the PAM/g-C3N4and PAM/g-C3N4-charcoal composite materials were analyzed using SEM technique. Photocatalytic reduction of chromium (VI) to chromium (III) was validated using the composites.